Diversity of DNA sequences detected by PCR based DNA fingerprinting, antibiotic resistance and plasmid profiles of Escherichia coli occurring in raw milk - Samuel, Lihan; Son, Radu; Gulam, Rusul; Karim, M.I.A.; Ooi Wai, Ling; Navies, Maisin (ORES, Malaysia, 1999)
Ninety five Escherichia coli strains isolated from raw milk were analyzed for plasmid profile and antimicrobial resistance, and typed by RAPD fingerprints. All the E. coli strains were resistant to four or more of the antibiotics tested. However, none were resistant to ceftazidime, gentamicin and norfloxacin. The multiple antibiotic resistance (MAR) index values of the E. coli strains ranged from 0.25 to 0.81, indicating that all were isolated from raw milk samples that were exposed to high risk sources. Plasmids of 1.4 to 68 MDa were detected in 69 (72.6%) of the E. coli strains examined. The detection of a single plasmid of 68 MDa in 58 of 69 plasmid containing strains limits the usefulness of plasmid profiles as an epidemiological marker. RAPD fingerprints of the 95 E. coli strains were obtained using two 10 mer primers, GEN15009 and GEN15010, to differentiate or identify clonal relationship among the strains examined. The dendrogram constructed from the combined results of the RAPD patterns obtained from both primers showed that the 95 E. coli strains were grouped into six major clusters, indicating that five major clonal lineages (clusters 1, 2, 3, 4 and 5) of E. coli strains were predominant in the raw milk samples tested.